DIMENSIONAL VERIFICATION AND QUALITY CONTROL OF IMPLANTS PRODUCED BY ADDITIVE MANUFACTURING - Teodor Toth; Radovan Hudak; Jozef Zivcak (Kvalita Inovácia Prosperita, 2015)
Purpose: Development of computer technology and alternative manufacturing methods in form of additive manufacturing leads to the manufacture of products with complex shapes. In the field of medicine they include, inter alia, custom-made implants manufactured for a particular patient, such as cranial implants, maxillofacial implants, etc. With regard to the fact that such implants are inserted into a patient’s body, it is necessary to perform the verification, including the shape and dimensional verification. The article deals with the application of the industrial computer tomography within the process of inspection and verification of selected custom-made implant types.Methodology/Approach: The Department of Biomedical Engineering and Measurement performs the verification of medicinal products manufactured by the additive manufacturing technologies from the Ti-6Al-4V (Grade 5) titanium alloy, using the coordinate measuring machine Carl Zeiss Contura G2 and the industrial computed tomography machine Carl Zeiss Metrotom 1500. These equipment fulfil the requirements for the identification and evaluation of dimensions of both, the external and the internal structures. Findings: The article presents the possibilities of the computed tomography utilisation in the inspection of individual implant manufacture using the additive manufacturing technologies. The results indicate that with the adjustment of appropriate input parameters (alignment), this technology is appropriate for the analysis of shape deviations, when compared with the CAD model.Research Limitation/implication: With the increasing distance of measured object from X-ray source, the machine’s resolution function decreases. Decreasing of resolution has a minor impact on the measured dimensions (relatively high tolerances), but has a significant impact on the evaluation of porosity and inclusions. Originality/Value of paper: Currently, the verification of a manufactured implant  can be carried out using 3D scanners and the industrial computed tomography. The use of 3D scanners is appropriate for the shape inspection, for example the shape of an implant’s outer surface. The computed tomography is the only method for evaluation of shape deviations, defectoscopy and dimensional analysis in one measurement.